Hydrophilic Films Based on Carboxymethylated Derivatives of Starch and Cellulose - Wilpiszewska, Katarzyna (Polymers (Basel), 2020)
The carboxymethylated derivatives of starch (CMS) and cellulose (CMC) were used for film preparation. The infrared spectroscopy revealed that crosslinking via ester bridges with citric acid occurred between the two polysaccharide derivatives. The effect of polysaccharide derivatives ratio on physicochemical properties of prepared films was evaluated. Generally, the values of tested parameters (moisture absorption, surface roughness, and mechanical and thermal properties) were between the values noted for neat CMS or CMC-based films. However, the physicochemical properties of the system with equal CMS/CMC weight ratio diverged from this trend, i.e., the highest tensile strength, the highest Young’s modulus (ca. 3.4 MPa and ca. 4.9 MPa, respectively), with simultaneously the lowest moisture absorption (18.5% after 72 h) have been noted. Such systems could potentially find application in agriculture or pharmacy.